2019
DOI: 10.1589/jpts.31.371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating gluteus maximus maximal voluntary isometric contractions for EMG normalization in male rugby players

Abstract: [Purpose] The aim of this study was to determine the highest electromyography (EMG) amplitude of the gluteus maximus from closed and open kinetic gluteal maximal voluntary isometric contractions (MVICs). [Participants and Methods] Ten healthy male rugby players performed three MVIC techniques that included, in random order: single leg squat, prone hip extension and standing gluteal squeeze. EMG signals were recorded from the inferior and superior regions of gluteus maximus of the dominant leg, and were normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Our study was conducted exclusively on high-performance female field hockey players, therefore limiting generalisation to this group as it only provided data on the participants’ dominant side. The use of sEMG is associated with limitations because of various influences on the sEMG signal amplitude such as cross-talk (Bishop et al 2018 ; Cochrane et al 2019 ; Serner et al 2014 ). Owing to the close proximity of the TFL muscle and gluteus minimus to Gmed, it is possible that these two muscles may contribute to the muscle activity recorded by the sEMG signal for Gmed (Distefano et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study was conducted exclusively on high-performance female field hockey players, therefore limiting generalisation to this group as it only provided data on the participants’ dominant side. The use of sEMG is associated with limitations because of various influences on the sEMG signal amplitude such as cross-talk (Bishop et al 2018 ; Cochrane et al 2019 ; Serner et al 2014 ). Owing to the close proximity of the TFL muscle and gluteus minimus to Gmed, it is possible that these two muscles may contribute to the muscle activity recorded by the sEMG signal for Gmed (Distefano et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only body weight rehabilitation exercises that are performed without any additional external load, such as a barbell, dumbbell, band and machine, as well as plyometric or hopping movements, were considered. The only studies that met these criteria were those of Boren et al ( 2011 ), Simenz et al ( 2012 ), Webster and Gribble ( 2013 ), Lee et al ( 2014 ), MacAskill, Durant and Wallace ( 2014 ), Kim and Yoo ( 2015 ), Jeon, Kwon and Weon (2016), Ebert et al ( 2017 ), Macadam and Feser ( 2019 ) and Cochrane, Gabriel and Harnett ( 2019 ). Cochrane et al ( 2019 ) was the only study conducted in a high-performance population, namely rugby players.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The order of the exercises was standardized to avoid displacement of the posterior electrodes by sitting on the electrodes while performing the knee extension before the kickback. All exercises were performed unilaterally using the left leg due to the design of the machines and one previous comparable study (Cochrane et al, 2019).…”
Section: Experimental Designmentioning
confidence: 99%
“…Further, the EMG amplitude of the semitendinosus and semimembranosus might be inhibited when combining extension of the knee and hip (Fujiwara and Basmajian, 1975;Yamashita, 1988). Regarding the hip extensor gluteus maximus, the only known study comparing EMG amplitude during back squats and hip extensions reported similar activity during the two exercises (Cochrane et al, 2019).…”
Section: Introductionmentioning
confidence: 99%